2018
DOI: 10.1186/s40691-018-0139-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risks and enjoyment of access-based consumption: identifying barriers and motivations to fashion renting

Abstract: Over-consumption has been identified as one of the major challenges facing sustainability in the fashion industry (Armstrong et al. 2015). Consumers keep purchasing fashion items more than is needed, which generate more wastes. This is especially true with the rising popularity of fast fashion. Consumers are now able to purchase more fashion products that are being used for a shorter period at a relatively lower cost. Although the fast fashion strategy makes it easier for consumers to purchase apparel products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 45 publications
7
89
4
Order By: Relevance
“…This result was somewhat expected due to the findings in previous literature [23]. It is because consumers mainly focus on the fun and enjoyment they experience from shopping, whereas the price rarely impacts on determining consumers' intentions to try fashion renting [79]. On the other hand, consumers who were sensitive to pricing did not consider that online fashion renting services could provide financial benefits to their consumption behavior.…”
Section: Discussionmentioning
confidence: 56%
“…This result was somewhat expected due to the findings in previous literature [23]. It is because consumers mainly focus on the fun and enjoyment they experience from shopping, whereas the price rarely impacts on determining consumers' intentions to try fashion renting [79]. On the other hand, consumers who were sensitive to pricing did not consider that online fashion renting services could provide financial benefits to their consumption behavior.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, Johnson et al (2016) have confirmed that attitude positively influences consumers' intention to participate in collaborative consumption. Lang (2018) found positive effects of attitude on consumers' intention to participate in fashion renting as well. In addition, attitude also positively influences the purchase intention of customized apparel products (Lang et al 2018).…”
Section: Theory Of Reasoned Action (Tra)mentioning
confidence: 88%
“…Second, this study is the first to explore the moderating role of contamination concern in the context of shared consumption, including FRS. Although scholars recognized contamination concern as a barrier to shared consumption ( Becker-Leifhold and Iran, 2018 , Lang, 2018 ), they concentrated on examining a negative relationship between contamination and acceptance of products (e.g., Argo et al, 2006 , Xu et al, 2014 ). The present study advances the existing literature, which simply focuses on how to reduce the negative impact of contamination concern of access-based consumption ( Hazée et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Measures of adoption intentions and attitudes were taken from Park and Joyner Armstrong (2019a) (e.g., “The likelihood I would use the rental service is high” for adoption intentions, and “I found the rental service is unfavorable/favorable” for attitudes). Functional value was measured with four items ( Lee & Chow, 2020 ); economic value with five items ( Guiot & Roux, 2010 ); green value with three items ( Lee & Chow, 2020 ); social value with three items ( Wang et al, 2018 ); and emotional value adopted from a five-item enjoyment scale ( Lang, 2018 ). Since our model treats economic value separately, one item (“Renting clothing online would enable me to get the apparel I want more cheaply”) was deleted from the functional value construct as it may overlap with economic value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation